2005
DOI: 10.1016/j.virol.2005.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macrophage and dendritic cell subset elimination on antiviral immunity, viral clearance and production of type 1 interferon

Abstract: We report herein that vesicular stomatitis virus (VSV) induced a concurrent primary Th1 (T helper 1) and Th2 cytokine response detectable ex vivo. Liposome-encapsulated clodronate-mediated elimination of CD8- marginal dendritic cells (DCs) and splenic macrophages (m Phi), but not CD8+ interdigitating DCs, prior to infection resulted in a markedly diminished chemokine and Th1 (IL-2, interferon-gamma) cytokine response, although the Th2 response (IL-4) remained relatively intact. Repopulation with marginal DCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 38 publications
4
36
0
1
Order By: Relevance
“…production is consistent with loss of this response following liposome-mediated suicide of phagocytic cells (32). Furthermore, a recent report demonstrated that both Ag-pulsed macrophages and DCs activate and induce effector functions in naive T cells upon adoptive transfer in vivo.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…production is consistent with loss of this response following liposome-mediated suicide of phagocytic cells (32). Furthermore, a recent report demonstrated that both Ag-pulsed macrophages and DCs activate and induce effector functions in naive T cells upon adoptive transfer in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, viral clearance is impaired in mice depleted of both splenic macrophages and DCs even though serum titers of type I IFN are within normal ranges (32). These different outcomes may be due to efficient clearance of VSV by splenic macrophages present in Tg mice rendered deficient of DCs but not macrophages.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…or s.c. administered therapeutic proteins should be processed by APCs in peripheral tissues and be transported to draining lymph nodes for presentation to immune effectors. Thus, the role of a specific type of APC in relation to immune response against a particular protein therapeutics remains to be surveyed in a systematic manner, as has been done in case of several pathogenic Ags (24,25). Inflammatory signals in mounting an immune response.…”
Section: Professional Apcs Are the First Immune-sensitive Depots For mentioning
confidence: 99%